THE QUALITY CONTROL USING SEVEN TOOLS METHOD FOR DEFECT PRODUCT ON SCANNER PRODUCTION - Zalfa Nur Halizah; Alfonsa Dian Sumarna (Jurnal Akunida, 2023)
The aim of this research is to analyze the achievement quality standards that have been set and reduce waste due to product defects in scanner production at PT. Epson Batam using seven tools method. This research using a quantitative and descriptive method. Quantitative method using check sheet, stratification, histogram, pareto diagram, scatter diagram and while descriptive method using fishbone analysis. Data was collected by observation and documentation techniques. The results of the study stated that the improvements implemented to reduce product defects that occur from several factors, namely materials and work methods, it is necessary to do an effective division of work time so defect product do not occur due to pursuing production targets and material factors that must be checked before the goods/products enter the market.